(untitled) (Journal of Pedagogical Inventions and Practices, 2022)
Cooperation between educational institutions, neighborhood and parents and their types of activities in the organization of the educational process have been clarified. The importance of their integration in organizing the process of forming students into socially active individuals and increasing their activity has been revealed.